Ellipses as Narrative Tools: Stylistic and Cohesive Functions in Jeffrey Deaver’s The Coffin Dancer: https://doi.org/10.5281/zenodo.17116489 - Abdul Hannan Majeed; Maryam Ibrahim; Ghulam Ali*; Ayesha Majeed (`, 2025)
In thriller literature, the manipulation of narrative elements such as pacing and suspense is crucial for maintaining reader engagement. This study explores the strategic use of ellipses in Jeffrey Deaver’s The Coffin Dancer, highlighting their dual role as both stylistic choices and cohesive devices. Through a qualitative content analysis grounded in Halliday and Hasan’s (1976) theory of cohesion, the research examines how ellipses influence narrative pacing, heighten suspense, enhance dialogue realism, and ensure structural continuity. By categorizing instances of ellipsis usage, the study reveals how Deaver adeptly balances fragmented sentence structures and deliberate omissions to mirror characters’ psychological states and the high- stakes environment typical of the thriller genre. Comparative insights with contemporaneous works, such as Lee Child’s Jack Reacher series, underscore the nuanced application of ellipses in Deaver’s narrative technique. The findings demonstrate that ellipses are integral to creating an immersive and tension-filled reading experience, reinforcing both the stylistic and cohesive integrity of the novel. This research contributes to a deeper understanding of punctuation as a powerful literary tool and suggests avenues for future studies across diverse genres to further elucidate the multifaceted functions of ellipses in narrative construction. Keywords: Ellipses, Narrative Cohesion, Stylistic Devices, Pacing, Suspense, Thriller Literature, Jeffrey Deaver, Dialogue Realism